2013
DOI: 10.1371/annotation/b38f50e0-04b6-42c5-8b19-50be747a38f3
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Nbn and Atm Cooperate in a Tissue and Developmental Stage-Specific Manner to Prevent Double Strand Breaks and Apoptosis in Developing Brain and Eye

Abstract: Nibrin (NBN or NBS1) and ATM are key factors for DNA Double Strand Break (DSB) signaling and repair. Mutations in NBN or ATM result in Nijmegen Breakage Syndrome and Ataxia telangiectasia. These syndromes share common features such as radiosensitivity, neurological developmental defects and cancer predisposition. However, the functional synergy of Nbn and Atm in different tissues and developmental stages is not yet understood. Here, we show in vivo consequences of conditional inactivation of both genes in neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…NBS organoids showed a dramatic reduction in p53 protein levels, with no differences in TP53 mRNA expression, consistent with our previous results using NPCs derived from NBS-iPSCs [ 21 ]. Strikingly, Nbn knockout mice or inducible Nbn null mice cells showed an activation of p53 stabilization [ 16 , 55 , 56 ]. This emphasizes that the use of neuronal cells derived from iPSC-derived from NBS patients can unveil new mechanistic insights underlying NBS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NBS organoids showed a dramatic reduction in p53 protein levels, with no differences in TP53 mRNA expression, consistent with our previous results using NPCs derived from NBS-iPSCs [ 21 ]. Strikingly, Nbn knockout mice or inducible Nbn null mice cells showed an activation of p53 stabilization [ 16 , 55 , 56 ]. This emphasizes that the use of neuronal cells derived from iPSC-derived from NBS patients can unveil new mechanistic insights underlying NBS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, several studies based on Nbn conditional knockouts and inducible Nbn -deletion mice have been generated. These studies identified proliferation arrest and increased apoptosis in the neural progenitor cells due to over-activation of p53, which ultimately leads to microcephaly [ 14 , 15 , 16 , 17 , 18 ]. Although these studies have provided helpful information, it is necessary to compare and bridge the gap between these mouse models and the human phenotype of NBS.…”
Section: Introductionmentioning
confidence: 99%
“…Later, other studies revealed that Nbn loss also compromised the visual system development, leading to a mild apoptosis of NPCs of the retina, demyelination of the optic nerves, and impaired retinal functions [334,335]. These studies also shed light in the functional interplay between NBS1 and ATM, revealing that, in the developing CNS, these proteins collaborate to prevent DSB accumulation and the apoptosis of progenitor cells in a tissue-and developmental stage-specific manner [335,336]. None of these studies interrogated the S-phase-specific or direct roles of NBS1 in the DNA replication of NPCs.…”
Section: Nijmegen Breakage Syndrome (Nbs)mentioning
confidence: 99%